Analysis on Application Prospect and Challenge of Nanomaterials in Environmental Protection - Zhou, Minqian (International Journal of Materials Science and Technology Studies, 2025)
This study aims to comprehensively analyze the application prospects and challenges of nanomaterials in environmental protection, providing theoretical support and practical guidance for the development of eco-friendly technologies. Through systematic review of domestic and international literature, this research systematically examines existing research achievements in environmental applications of nanomaterials while analyzing their unique properties. The findings indicate that nanomaterials have achieved notable successes in water, air, and soil pollution control, demonstrating broad application potential such as innovative pollutant monitoring technologies and multifunctional eco-materials. However, implementation faces multiple challenges including cost control in production processes, technical barriers in large-scale manufacturing, ecological toxicity and biodiversity impacts, as well as regulatory gaps and incomplete policies. To address these issues, the study proposes strategies encompassing low-cost production technology development, overcoming mass production challenges, establishing environmental risk assessment systems, enhancing ecological monitoring and research, promoting policy formulation, and improving regulatory frameworks which all aimed at advancing sustainable application of nanomaterials in environmental protection.